O‐Doped Nanographenes: A Pyrano/Pyrylium Route Towards Semiconducting Cationic Mixed‐Valence Complexes. Issue 10 (24th January 2020) - Ðorđević, Luka; Valentini, Cataldo; Demitri, Nicola; Mézière, Cécile; Allain, Magali; Sallé, Marc; Folli, Andrea; Murphy, Damien; Mañas‐Valero, Samuel; Coronado, Eugenio; Bonifazi, Davide
Abstract: Herein we report an efficient synthesis to prepare O‐doped nanographenes derived from the π‐extension of pyrene. The derivatives are highly fluorescent and feature low oxidation potentials. Using electrooxidation, crystals of cationic mixed‐valence (MV) complexes were grown in which the organic salts organize into face‐to‐face π‐stacks, a favorable solid‐state arrangement for organic electronics. Variable‐temperature electron paramagnetic resonance (EPR) measurements and relaxation studies suggest a strong electron delocalization along the longitudinal axis of the columnar π‐stacking architectures. Electric measurements of single crystals of the MV salts show a semiconducting behavior with a remarkably high conductivity at room temperature. These findings support the notion that π‐extension of heteroatom‐doped polycyclic aromatic hydrocarbons is an attractive approach to fabricate nanographenes with a broad spectrum of semiconducting properties and high charge mobilities. Abstract : My O my ! O‐doped nanographenes derived from the π‐extension of pyrene are reported. The compounds are highly fluorescent and feature low oxidation potentials. Electric measurements of single crystals of mixed‐valence salts show a semiconducting behavior with a remarkably high conductivity at room temperature.